Assessing changes in travel behavior induced by modified travel times: a stated adaptation survey and modeling approach. - Weis, Claude; Axhausen, Kay W. (Routledge, 2012)
The paper reports on research exploring a stated adaptation approach for analyzing changes in travel behavior brought about by changes in travel times. A sample of respondents returned a five-day travel diary, from which one day was selected for further analysis. The conditions of the reported day were modified using predefined heuristics to attain significant changes in the travel time of the reported trips. The respondents were then presented with these hypothetical scenarios in faceto-face interviews and asked to state how the implied changes would have affected their activity scheduling on the specified day and then to adapt their reported schedule. The data was used to estimate models of scheduling adaptations. A series of models was used to assess the adaptations stated by the respondents. At the core is a Multiple Discrete-Continuous Extreme Value (MDCEV) model, which is used to predict how the respondents compensate for the gained or lost time. The adaptations to the respondents' schedule were surprisingly sparse despite the substantial changes in generalized costs imposed by the scenarios. The most frequent adaptations were changes in departure time from the home location, and mode or destination changes to recover the lost time. The expected changes, concerning the number of conducted trips and activities and their combination into home-tohome tours, were extremely rare. Respondents were very selective when making adaptations to their routine, even under extreme circumstances. The paper describes the survey approach, which is to the best of our knowledge novel in its application, and reports the model results of the respondents' reactions to the changes implied in the household interviews and provides an example of the potential application of the results.
Keywords: Verkehr; Verkehrsplanung; Verkehrsverhalten; Reisezeit; Forschungsprojekt; Modellversuch